Developing an e-learning strategy at Wrocław University of Economics in 2008-2009 - Unold, Jacek (Rozwój strategii e-learningowej na Uniwersytecie Ekonomicznym we Wrocławiu w latach 2008-2009, 2011)
Electronic learning has always been considered a highly sophisticated form of education. Wroclaw University of Economics began to introduce e-learning in early 2008. Nearly two years of enormous collective effort brought about significant results in this important domain. This article discusses the most important guidelines for the implementation strategy. It presents the historical aspects of distant education and the opening situation at WUE in 2008. Then, it identifies the key thematic areas responsible for the successful implementation effort. The first stages of the strategy implementation are followed by the initial results in this domain
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 202, s. 97-104
Keywords: distance learning history; electronic learning (e-learning); Moodle platform; implementation strategy; E-learning Centre